Menanamkan Nilai-nilai Akhlak dalam Pergaulan Siswa Di Lingkungan Madrasah - Kholik, Moh.; Mujahidin, Mujahidin; Munif, Achmad Abdul (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This research examines the application of Islamic social etiquette among students at MTs Al-Ikhlas Alang-Alang Caruban Jogoroto Jombang. The research method used is a qualitative approach with a case study type. The research results show that this madrasa applies Islamic social etiquette through preventive and repressive measures. Preventive measures include education in aqeedah, worship, and morals. Repressive action takes the form of giving educational punishment. The main supporting factor is the teacher's role as a guide, facilitator, role model, and motivator. The inhibiting factor is the influence of social media and technology. Implementing Islamic social etiquette is urgent to shape students' personalities with good morals, produce a young generation with a leadership spirit, and anticipate the negative influence of developments in technology and social media. Strategies to strengthen its implementation include increasing the quality and quantity of religious activities, collaboration with parents, separate seating for men and women, teacher supervision, and spiritual formation through habituation to commendable behavior and imitating the Prophet Muhammad SAW.